BPEL4PEOPLE Anti-Patterns: Discovering Authorization Constraint Anti-Patterns in Web Services - Holanda, Henrique J. A.; Marques, Carla K. de M.; Pinto, Francisca Aparecida P.; Guéhéneuc, Yann-Gaël (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2018: Anais do III Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2018.3474, 2018)
Despite the abundance of analysis techniques to discover antipatterns in BPEL, there is hardly any support for authorization constraint errors in web services orchestrated by BPEL4People. Most techniques simply abstract from people (human user interactions), while people dependencies can be the source of all kinds of errors. This paper focuses on the discovery authorization constraint anti-patterns in web services orchestrated by BPEL4People. We present an analysis approach that is expressed in terms of rule card, the wellknown, stable, adaptable, and effective model-checking techniques can be used to discover authorization constraint errors. Moreover, our approach enables a seamless integration of control-flow and authorization constraint verification.